Ocular involvement and visual prognosis in juvenile idiopathic arthritis associated uveitis - Gonçalo Cavaco Tardão; Pedro Carreira; Filipe Moraes; Rita Carreira; Tomás Loureiro; Ana Vide Escada; Maria José Santos; Ana Melo Cardoso; Nuno Campos (International Journal of Ophthalmology)
AIM: To characterize a Portuguese population of patients with juvenile idiopathic arthritis (JIA) and to evaluate possible associations between clinical factors and ocular involvement. METHODS: Patients diagnosed with JIA in the previous 20y in Hospital Garcia de Orta were included. Data were assessed from Reuma.pt database. Associations between demographic (age and sex), clinical (articular involvement, extra-articular manifestations, biological therapy), laboratory data [anti-nuclear antibodies, anti-cyclic citrullinated peptide (CCP) antibodies, rheumatoid factor, human leukocyte antigen B27 (HLA-B27), C-reactive protein, erythrocyte sedimentation rate] and ocular involvement were assessed. Statistical analysis was performed using Chi-square for categorical variables and Mann-Whitney test for continuous variables. RESULTS: Totally 91 patients were included, 11 (12%) with previous episodes of uveitis. There was a statistically significant preponderance of early age at JIA diagnosis (mean 4.73 vs 9.58y, P=0.008), antinuclear antibodies positivity (P=0.01), and oligoarticular subtype (P=0.04) in the Juvenile idiopathic arthritis-associated uveitis (JIA-U) group. Ocular complications occurred in 36.4% of patients (n=4): cataracts (n=2), band keratopathy (n=1) and posterior synechiae (n=1). The occurrence of complications was corelated with a shorter period between JIA diagnosis and the first JIA-U episode (mean 0.67 vs 4.88y, P=0.012) but not with age at JIA diagnosis or articular involvement. There was erythrocyte sedimentation rate elevation in the 12mo preceding uveitis (mean 40.5 mm/h, range 13-83). CONCLUSION: The occurrence of JIA-U shortly after JIA diagnosis is shown to be a potential risk factor for ocular complications.